THE IMPLEMENTATION OF STANDARD EDUCATION PROCESS IN ISLAMIC EDUCATION AND CHARACTER AT SMA NEGERI 17 MAKASSAR - Asrar, Muh.; Mustami, Muh. Khalifah; Muzakkir, Muzakkir; Rahman, Ulfiani (Program Pascasarjana, UIN Alauddin Makassar, 2021)
This study aims to describe and analyze the process of implementing standard educational processes in Islamic religious education and Characters subjects (PAI and Budi Pekerti) at SMA Negeri 17 Makassar, the supporting and inhibiting factors for implementing educational process standards, and the success rate of implementing Standard Education Process in supporting the success of Islamic Education and Character at SMA Negeri 17 Makassar. Qualitative research is included in this study. The method employed is Pedagogical. Teachers of Islamic religious education, school principals, education unit supervisors, and associated papers were used as data sources. Data was collected using the methods of observation, interviews, and documentation. Data analysis was carried out in three stages: data reduction, data presentation, and drawing conclusions. Testing the validity of the data is done by increasing persistence, doing triangulation, discussing with colleagues, and member checking. An important finding in this study is that the process of implementing the standard educational process on subjects of Islamic religious education and manners at SMA Negeri 17 Makassar begins with the preparation of a lesson plan. It refers to the Standard Education Process in terms of types, procedures, principles, and components in the lesson plan. After preparing the plan, the teacher carries out the learning process using a scientific approach and learning models that are relevant to the Standard Education Process. Furthermore, the teacher analyses the learning process and results both during and after the learning process takes place using authentic assessments and other forms of assessment appropriate to the domains of attitudes, knowledge, and skills.